Voltage Quality Enhancement in Microgrid Through Customized Synchronous Reference Frame Theory Based Upgraded Dynamic Voltage Restorer - Ayesha Ayoub; Muhammad Siddique; Ahsan Iqbal; Hassan Ali (Pakistan Journal of Engineering & Technology, 2020)
Microgrid (MG) offers an elaborate list of solutions to solve the common problems associated with local distribution systems. These problems are mainly reliability issues. Researchers are trying to develop improvements in its properties and features to overcome these problems as well as the ones regarding power quality (PQ). The standard microgrid structure does not support power quality compensation strategies, which is why there are distribution system issues related to it.  Implementations of the DVR have been proposed at both a low voltage (LV) level, as well as a medium voltage (MV) level; and give an opportunity to protect high power sensitive loads from voltage sags, because it is a very efficient. We have proposed in this paper about the Upgraded Dynamic Voltage Restorer (UDVR) and mentioned that it I will provide a convenient solution to the voltage sag and swell in grid-connected microgrid problems. A microgrid structure provides a reliable distribution system for local loads on the other side, UDVR allows a sag/swell free power supply for loads. This control via UDVR comes from a fuzzy technique system and an Upgraded Synchronous Reference Frame (USRF) concept. The dynamic compensation characteristics of UDVR are applied to voltage transient disturbance analysis under various run conditions. The proposed control system's stability is also analyzed. The entire system is manufactured by utilizing the MATLAB/Simulink environment. The results of the simulation confirmed the performance of UDVR under the proposed control approach. Simulation results prove that the proposed method is correct and has better real-time and compensation flexibility.